Pengembangan Bahan Ajar PKn Berbasis Neurosains Pada Siswa Kelas III Sekolah Dasar - Asnita Asnita (Institut Agama Islam Negeri Palopo, 2020)
Research is conducted with the aim to determine the design and effectiveness of teaching materials according to the assessment of the class and teachers in the field of study (PKn and neuroscience) and student learning activities in the classroom. The research method used in this research is Research & Development (R&D). The development Model used in developing 4-D product is composed of 4 stages, namely define, design, develop, and disseminate. Teaching materials developed in the form of self-esteem material. The subject in this research is a class III student of 24 ways to obtain the data in this study: validation sheet, student observation sheet and student learning test. The Data obtained is analyzed using a descriptive statistical analysis. In the analysis of the Council is used descriptive statistics. The results of this study show that the teaching materials in the form of neuroscience-based teaching books are said to be valid by three validators. Based on the results of the data analysis obtained a valid learning device through the validity analysis for the teaching materials of 3.34 and included in the valid category.